The antiquity of knowledge and its development caused by environmental changing / Noor Aqila Shahrina Johan Shah and Siti Nurbaizura Ram - Johan Shah, Noor Aqila Shahrina; Ram, Siti Nurbaizura (Faculty of Information Management, 2015)
This article is related to what general knowledge is about and how the knowledge gets started and grows. Besides that, is about the history of knowledge starting from the previous century. When the knowledge is expanded there was disseminating information to be shared with the people. The rapid change of demand and the rapid growth of knowledge is also discussed in the article as they are inter-related with the growth and the development of knowledge. There are agencies also involved in providing information to people which require the latest information. The purpose of this article is to examine how the rapid growth of knowledge occurred and want to know about the knowledge that rapid changes occurring on request.